The role of the miR1976/CD105/integrin αvβ6 axis in vaginitis induced by Escherichia coli infection in mice - Lisha Jiang (Scientific Reports, 2019)
Abstract Vaginitis is very common among women, especially women of childbearing age, and is associated with significantly increased risk of preterm birth and pelvic inflammatory diseases. An imbalance in the vaginal flora, the primary cause of vaginitis, promotes the initiation and progression of vaginal infections. However, the responsible mechanisms are still poorly understood. Using a murine vaginitis model of Escherichia coli infection, we demonstrated that decreased expression of microRNA1976 and increased expression of CD105 and integrin αvβ6 were closely associated with the progression of vaginal infection. Importantly, we demonstrated for the first time that the microRNA1976/CD105/integrin αvβ6 axis regulates E. coli-mediated vaginal infection in mice, as evidenced by the finding that E. coli-induced vaginal infection was reversed by microRNA1976 overexpression and exacerbated by CD105 overexpression. The regulation of CD105 and integrin αvβ6 by microRNA1976 was further confirmed in a murine model of vaginitis with adenoviral vector treatment. Taken together, our data suggested that microRNA1976 negatively regulates E. coli-induced vaginal infection in mice at least in part by suppressing CD105 and integrin αvβ6 expression. These findings may provide new insight into the mechanisms of E. coli-induced vaginitis, identify a novel diagnostic biomarker and a potential therapeutic target for flora imbalance-associated vaginitis.